Coping Strategies of BEED Teaching Interns During Classroom Demonstration - Duldulao, Rica Mae; Naparan, Genesis; Remotigue, Donnelle Niño M.; Sanayon, Alyannah D. (Papanda Publisher, 2023)
Prospective teachers usually conduct classroom demonstrations during a teaching internship for one semester. Thus, teaching interns then perform actual teaching among students at varying grade levels. This study investigated the challenges and coping strategies of BEED teaching interns in the western part of the Philippines. In this study, the researchers employed a single-case study model method of Sharan B. Merriam. Triangulation of data was also employed to validate the results of the study. They gathered the data through one-to-one interviews with BEED teaching interns who conducted classroom demonstrations on-campus and off-campus, four corresponding cooperating teachers, and the instructor of the research participants. Following the data analysis of Braun and Clarke (2008), the results revealed that these teaching interns experienced different challenges. These challenges involved difficulty in classroom management and difficulty in creating learning objectives. However, they showed positivity in their performance and applied the right coping strategies to lessen their burden. Among these coping strategies were using effective classroom management strategies, being confident, and asking assistance from their cooperating teacher to cope with those challenges. Through these experiences, teachers learned to adjust and cope with their challenges. Thus, they became better teaching interns. These findings are original and contribute to the plans and programs of the Commission of Higher Education in broadening the knowledge and developing the skills for improving student teacher’s academic success.